Neglected Tropical Diseases in Pakistan: A Story of Neglect - Khan, Aisha; Tariq, Mehreen; Simsek, Sami; Afzal, Muhammad Sohail; Fasihi Harandi, Majid; Ali, Shahzad; Ahmed, Haroon (Iranian Scientific Society Medical Entomology, 2020)
[Abstract Not Available]